Statistics on the operations at the Department of Urology, Toyota Memorial Hospital during an 11-year period (1987-1997) - Tamaki, M (Hinyokika kiyo. Acta urologica Japonica, 1999)
A clinical statistic survey was carried out on the operations performed at our Hospital from 1987 through 1997. The total number of operations was 3,383 and the number of operations excluding extracorporeal shock wave lithotripsy (ESWL) was 1,672, consisting of 227 (13.6%) operations of the kidney and ureter, 194 (11.6%) operations of the bladder, 481 (28.8%) operations of the prostate and urethra, and 705 (42.2%) operations of the penis and scrotal contents. Since new endourological technology and ESWL were developed for clinical application, the mode of operation has dramatically changed during the last 11 years, trending toward minimally invasive surgery